South Sudan Country Integrated Fiduciary Assessment, Volume 2. Public Finance Management Assessment - World Bank (Washington, DC, 2014)
The purpose of this Country Integrated Fiduciary Assessment (CIFA) is: (i) to assess the quality of public finance management and procurement systems in South Sudan; and (ii) to then determine the extent of fiduciary risk posed to domestic and external tax payers by the government's use of their funds through these systems. South Sudan has great potential for further increases in living standards, but achieving them will require large improvements in public services, both in access and in quality. In turn, Public Finance Management (PFM) and procurement systems need to be strengthened in order to improve public services; this will require linking spending more tightly to policy objectives and strengthening the operational efficiency of expenditures. In sum, strengthened PFM and procurement systems are not an end in themselves but, rather, the necessary means to achieving the ultimate objective: improved service delivery in South Sudan. This CIFA will be used by the Government of the Republic of South Sudan (GRSS) and by the country state governments to inform their design or reforms of PFM and procurement systems and, in the case of development partners, to inform their design or revision of technical and financial assistance programs and projects in support of the reforms.